The Influence Mechanism of Deformation on the Precipitation Behavior and Mechanical Properties of 7075 Aluminum Alloy During Hot Forming-Quenching Integrated Process - Huanhuan Li; Xinhang Zhang; Wei Dai; Wei Yan; Chaomei He; Jiake Luo; Mengxing Li; Ruolin Wu; Dang Wang (Metals)
The hot forming-quenching integrated process (HFQ®) organically combines the deformation and heat treatment, which can improve the forming performance of aluminum alloy while ensuring the final strength of formed parts. Thermal deformation in HFQ® has a non-negligible influence on precipitation behavior in subsequent artificial aging treatment and affects the mechanical properties of the formed parts. In this study, the relationship between the precipitation behavior and thermal deformation ratios was investigated. Results indicated that the formation temperatures of η′ and η decreased with an increasing deformation ratio; however, the former decreased more than the latter. The activation energy of η′ precipitation decreased linearly with increasing deformation ratio. Additionally, the phase transition fraction of η′ increased with the deformation ratio, leading to shorter times required to reach equivalent phase transition fractions. Deformation accelerated the phase transition of η′, and greater deformation resulted in a shorter transition time. The aging time required for peak Vickers hardness decreased with increasing deformation ratio, reflecting the promotion of precipitated phase formation and transformation by introduced dislocations. Consequently, peak hardness and yield strength were achieved in shorter aging times. In terms of industrial applications, this discovery offers significant advantages for shortening the production cycle of the hot stamping process and reducing production costs.